Asset-Liability Management in Banks: Concepts and Cases - Gindodiya (Prapti) Ed. ("52, Nagarjuna Hills,Hyderabad - 500 082", 2006)
Asset-Liability Management in Banks
50
Keywords: Asset-Liability Management in Banks